1995
DOI: 10.1016/0968-0896(95)00001-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-imidazolidinylidene propanedinitrile derivatives as stimulators of gastrointestinal motility—III

Abstract: Recently, we reported that a ranitidine derivative 2 (fumarate: KW-5092), which had a 2-imidazolidinylidene propanedinitrile moiety (A), showed potent gastrointestinal motility enhancing activity. We have also found that introduction of substituents such as benzyl or 4-fluorobenzyl (i.e., giving 3 or 4) at the N-3 position of the moiety (A) significantly increased this activity. In this study, novel 2-imidazolidinylidene propanedinitrile derivatives possessing a thioether 5-15 were prepared and evaluated for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…One of the most promising approaches for treating this disease is to enhance the acetylcholine level in the brain using AChE inhibitors [ 22 ]. AChE activity is also related to intestinal motility and AChE inhibitors are administered to treat dysphagia, gastric stasis achalasia, abdominal pain, paralytic ileus, vomiting, and constipation [ 39 ]. Several plants belonging to the Ericaceae family have shown a very strong activity against AChE and BuChE [ 38 ]; however, to our knowledge, no previous studies had been reported for the infusions or decoctions of Erica species.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most promising approaches for treating this disease is to enhance the acetylcholine level in the brain using AChE inhibitors [ 22 ]. AChE activity is also related to intestinal motility and AChE inhibitors are administered to treat dysphagia, gastric stasis achalasia, abdominal pain, paralytic ileus, vomiting, and constipation [ 39 ]. Several plants belonging to the Ericaceae family have shown a very strong activity against AChE and BuChE [ 38 ]; however, to our knowledge, no previous studies had been reported for the infusions or decoctions of Erica species.…”
Section: Resultsmentioning
confidence: 99%
“…Gut hydration is important in establishing a proper aqueous environment for the enzymatic digestion and absorption of nutrients, and to provide surface lubrication to propel intestinal contents by the peristaltic movements (Hirota and McKay, 2006). Conditions that may be associated with disturbances of the gastrointestinal motility and treated with AChE inhibitors include dysphagia, gastric stasis achalasia, abdominal pain, paralytic ileus, vomiting and constipation (Sasho et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The AChE inhibitor neostigmine is used to treat conditions related with impairment of gastrointestinal motility such as colonic pseudo-obstruction (Ponec et al, 1999) and post-operative impairment after colorectal surgery (Kreis et al, 2001). Other AChE inhibitors are also used to treat gastric motility dysfunctions such as metochlopramide and vinitidine (Sasho et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Three patents from Kyowa Hakko Kogyo and Millennium Pharmaceuticals claim imidazolidines as CXCR3 antagonists. These compounds have their origins in a series of acetylcholine esterase inhibitors. Data has been reported from screening at a single concentration in a radioligand binding assay with 125 I-CXCL10, which indicates that most compounds claimed in the patents have a pIC 50 of greater than 5.0 and provides some limited SAR. There is no conclusive evidence that either company still has an interest in the area, and there has been no further appearance of the compounds in the literature.…”
Section: Progress With Cxcr3 Antagonistsmentioning
confidence: 99%